1977
DOI: 10.1139/y77-008
|View full text |Cite
|
Sign up to set email alerts
|

Nonshivering thermogenesis in the rat. I. The relation between drug-induced changes in thermogenesis and changes in the concentration of plasma cyclic AMP

Abstract: Barbital-sedated, cold-acclimated (CA) or warm-acclimated (WA) rats were given different doses and combinations of noradrenaline, theophylline, and the adrenergic-blocking agents propranolol and phentolamine, to stimulate or inhibit calorigenesis in various ways. To see whether the effects of these drugs on calorigenesis could be ascribed to effects on the adenylate cyclase (EC 4.6.1.1) - cyclic AMP system, and to try to assess thereby the significance of this system in the regulation of nonshivering thermogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These findings are partly supported by the data described by Foster et al (1977), indicating higher plasma cyclic AMP levels in warm acclimated rats as compared to cold accli¬ mated rats. It was suggested that the changes in cyclic AMP levels are related to the changes in the rate of liver degradation and liver regeneration occurring during the period of heat exposure (Chayoth et al 1977).…”
supporting
confidence: 81%
“…These findings are partly supported by the data described by Foster et al (1977), indicating higher plasma cyclic AMP levels in warm acclimated rats as compared to cold accli¬ mated rats. It was suggested that the changes in cyclic AMP levels are related to the changes in the rate of liver degradation and liver regeneration occurring during the period of heat exposure (Chayoth et al 1977).…”
supporting
confidence: 81%
“…One of the means by which catecholamines enhance metabolism is through stimulation of adenylate cyclase resulting in formation of 3′, 5′ adenosine monophosphate in target tissues (Lundholm et al 1968;Robison et al 1971). Indeed, Foster et al (1977) demonstrated a close parallelism between changes in plasma cAMP and calorigenic responses to norepinephrine in cold acclimated rats.…”
mentioning
confidence: 90%